Do we need to improve breast cancer education? Attitude towards breast self-examination and screening programmes among Polish women - Poniedziałek, Barbara; Rebelka, Magdalena; Makowska, Kinga; Piotrowska, Justyna; Karczewski, Jacek; Rzymski, Piotr (Journal of Medical Science, 2014)
Introduction. Breast cancer is a global health threat which requires systematic basic health education and increasing the public attention and awareness. Therefore, breast self-examination (BSE), however controversial, was largely promoted in many countries including Poland. Moreover, the national breast screening programmes (BSP) were made available to general public. Aim. The study investigated the attitude towards BSE, BSP and breast cancer as a health threat among Polish women in relation to age, education, place of living and economical status. Material and methods. An anonymous questionnaire was completed by 751 Polish women. The results were statistically elaborated.Results. The majority of women declared to know how to perform BSE but only a small part (older females) practiced it regularly (once a month). National BSP were acknowledged by most of surveyed. The higher awareness of BSP was found for women with higher education and economical status whereas the lowest – for women inhabiting small villages and performing BSE rarely or never. Medical doctors and other medical staff were an insignificant source of BSP. Most of responders recognized breast cancer as a serious health threat in Poland. Conclusion. The general awareness of BSP and BSE among Polish women is satisfactory, yet the percentage of females performing BSE on regular basis remains too low. There is a need to increase the contribution of medical staff in breast cancer education and control activities.